2015
DOI: 10.1177/0269215515579421
|View full text |Cite
|
Sign up to set email alerts
|

Do lifestyle restrictions and precautions prevent dislocation after total hip arthroplasty? A systematic review and meta-analysis of the literature

Abstract: A more liberal lifestyle restrictions and precautions protocol will not lead to worse dislocation rates after total hip arthroplasty, but will lead to earlier and better resumption of activities and higher patient satisfaction. These results appear to hold up for various surgical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 27 publications
(94 reference statements)
1
34
0
2
Order By: Relevance
“…One third of the respondents indicated that resuming was permitted whenever the patient felt ready, and this was unrelated to the surgical technique. This seems in line with a recent review stating that Ba more liberal lifestyle restrictions and precautions protocol will not lead to worse dislocation rates, but instead will lead to earlier and better resumption of activities and higher patient satisfaction^ [24].…”
Section: Limitations and Strengths Of The Studysupporting
confidence: 84%
See 1 more Smart Citation
“…One third of the respondents indicated that resuming was permitted whenever the patient felt ready, and this was unrelated to the surgical technique. This seems in line with a recent review stating that Ba more liberal lifestyle restrictions and precautions protocol will not lead to worse dislocation rates, but instead will lead to earlier and better resumption of activities and higher patient satisfaction^ [24].…”
Section: Limitations and Strengths Of The Studysupporting
confidence: 84%
“…It covers demographic questions (questions 1-7) and questions on the three objectives: (i) surgeons' views on patients' perspectives of SF related issues (questions 8-11); (ii) surgeons' practises in addressing SF issues and perceived barriers to communication (question [12][13][14][15][16]; and (iii) surgeons' opinions on safe return to sexual activity after THA (question [17][18][19][20][21][22]. Finally, there were some additional questions (questions [23][24][25][26]). An in English translated version can be found in Appendix 1.…”
Section: Development Of Questionnairementioning
confidence: 99%
“…They concluded that restrictions are not effective in any approach after THR. 26 Pre-and postoperative tests were conducted by an independent physical therapist. Patients were allowed to choose their own physical therapist.…”
Section: Discussionmentioning
confidence: 99%
“…supine lying position, using walking aids, avoiding bending the hip joint by over 90 degrees) do not lead to lower rates of luxation. On the contrary, patients who were given more lenient behavioral restriction recommendations (»not sitting with crossed legs«) or none at all resumed activities earlier and showed a greater level of satisfaction (van der Weegen et al 2015). The 2010 Barmer GEK Hospital Report investigated the quality of life of selected insured patients and their level of outcome satisfaction following THA or TKA treatment by means of a written, retrospective and multidimensional survey.…”
Section: Post-discharge Treatment Outcomesmentioning
confidence: 99%